Vozes do poder: A influência dos mitos no modo de viver dos povoados rurais do município de Cametá- PA - Moia, Mix (2020)
The influence of myths on the way of life of rural black villages in the municipality of Cametá-PA, is a work resulting from the master's research by Professor Mix de Leão Moia, developed in the postgraduate program in Communication, Language and Culture, from UNAMA. This, clearly brings the influence of mythic narratives present in black villages in communities on the banks of the Tocantins River, municipality of Cametá, Pará, showing all the Amazonian quilombola culture present in narratives, which emerge as forms of power, coercion and social control in the spaces in which they are inserted. These are the (po) ethical voices that come from the charms of the forests and have echoed for generations in the quilombola communities of the Cametá region through the art of speaking and looking. Working with the oral history and life stories of deponents who live in the community of Mola and Tomázia, Professor Mix de Leão Moia does a thorough job with social / collective memory, describing, in a wealth of details, in accessible language, the nuances of the life stories of the people who live in the place, demonstrating through the stories of the “Pant Wet” how much the mythical narrative is used as a mechanism of social control, showing that such narrative has an implicit moral for determining habits, prescriptions and vetoes in a space not delimited by fences and wires, but which has a tireless “watchman” that since the time when the place housed fugitive blacks, protects the place, because after all no one enters and no one leaves without first knowing or hearing about the myth of the Pants Wet. Therefore, I invite all readers who seek to know about quilombola culture, especially linked to the studies of mythic narratives to address these voices that count on enchantment within the forests.